2022
DOI: 10.3390/nano12152538
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of N and Fe-Doped TiO2 Nanoparticles for 2,4-Dimethylaniline Mineralization

Abstract: The present study aimed to evaluate the feasibility of developing low-cost N- and Fe-doped TiO2 photocatalysts for investigating the mineralization of 2,4-dimethylaniline (2,4-DMA). With a single anatase phase, the photocatalysts showed high thermal stability with mass losses of less than 2%. The predominant oxidative state is Ti4+, but there is presence of Ti3+ associated with oxygen vacancies. In materials with N, doping was interstitial in the NH3/NH4+ form and for doping with Fe, there was a presence of Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 61 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Nguyen et al found that the crystallite diameter for Pd-doped TiO 2 is in the range of 12-28 nm by measuring 20 particles using the ImageJ program [15]. It has been reported that nanoparticles with size ≤ 100 nm are more active against organic pesticides than higher nanoparticles, associated with an increase in surface area [33,34].…”
Section: Transmission Electron Microscopy (Tem) Studiesmentioning
confidence: 99%
“…Nguyen et al found that the crystallite diameter for Pd-doped TiO 2 is in the range of 12-28 nm by measuring 20 particles using the ImageJ program [15]. It has been reported that nanoparticles with size ≤ 100 nm are more active against organic pesticides than higher nanoparticles, associated with an increase in surface area [33,34].…”
Section: Transmission Electron Microscopy (Tem) Studiesmentioning
confidence: 99%